Wieloproblemowość sytuacji kryzysowych a system wsparcia - Kotlarska-Michalska, Anna (Kultura-Społeczeństwo-Edukacja, 2022)
The article contains considerations on the possibility of treating a crisis situation as a result of other problems and difficulties, sometimes hidden, which previously occured, that contribute to the weakness and inability of a human being to continue functioning. The assumption that a crisis situation is a complex combination of many problems allows for a different view of the support system. The article presents arguments in favor of recognizing a crisis situation as a state of multiple problems a person cannot cope with on their own. The main features of the support system as part of crisis intervention and some imperfections of its functioning were also characterized.